Nurturing Excellence: Leveraging Service Quality for Competitive Advantage in Islamic Boarding Schools - Diana, Sevia; Zaini, Abdul Wahid (Al-Qalam Institue, 2023)
This study illustrates the quality of service in building competitive advantage in Nurul Jadid Islamic Boarding School. This research uses a qualitative case study approach. Data were obtained from observations and interviews. The resource persons in this study amounted to seven people and consisted of leaders of the Nurul Jadid Islamic boarding school, bureau leaders, bureau staff, students, guardians, alumni and the community around the Nurul Jadid Islamic boarding school. Data analysis using Miilles and Hubberman data reduction, data display and data verification. The results obtained from the application of service quality in building competitive advantage at Nurul Jadid Islamic Boarding School are (1) Tangible: real services such as E-Bekal services, BPS, student visits, goods deposit services, and so on, (2) Reliability: services in the form of reliability such as TOEFL test services, service SOPs, service regulations, teacher centralization, etc., (3) Responsiveness: responsive services or complaints from guardians in the form of guardian groups, (4) Insurance: health insurance, employment and pension security, (5) Empathy: the role of guardians for students